Mindfulness or expectancy? The label of mindfulness leads to expectancy effects - Noshari MG; Kempton HM; Kreplin U (John Wiley and Sons Ltd on behalf of British Association for Counselling and Psychotherapy, 2023)
The increasing popularity of mindfulness practices has seen an accompanying growth in research that includes the development of several self-report mindfulness measures. However, while caution has been recommended in the use of these self-reports, there has been little direct assessment of their susceptibility to expectancy effects. This research aimed at understanding whether expectancy effects exist for self-reported mindfulness measures (Study 1; n = 60), and how expectancy effects might manifest in relation to positive and negative expectancy (Study 2; n = 60). The first study manipulated whether (i) the task (jigsaws) was labelled as “mindfulness,” and (ii) whether “authentic” mindfulness instructions were given. Given any increases in self-reported mindfulness might potentially occur due to engaging in the mindful and attentionally demanding task, the second study manipulated whether the introduction placed mindfulness in a positive or negative context. A pre-/post-test design was employed using the Five Facet Mindfulness Questionnaire and Applied Mindfulness Process Scale self-report measures for mindfulness and the Perceived Stress Scale for well-being. The findings revealed expectancy effects for simply using the term mindfulness and that the direction of effects could be manipulated. This research suggests that researchers need to be cautious in evaluating self-reports of mindfulness practice due to expectancy effects, especially in the context of brief interventions without objective measures.